In vivo antibody discovery and hybridoma technology - Hanack, Katja (Henry Stewart Talks, 2022)
Antibodies, The immune response, Monoclonal antibodies, Monoclonal antibody generation, Immunisation, Hybridoma technology, Antigen analysis, In vitro immunisation, Monoclonal antibody characterization, ELISA, Immunofluorescence, HAT selection, Laser-Enabled Analysis and Processing (LEAP), Screening for hybridoma cells, Isotype-specific screening